Heteroglossia in The Implementation of Language Policy on Campus Public Signs - Paramarta, I Made Suta; Artawa, Ketut; Satyawati, Made Sri; Purnawati, Ketut Widya; Suputra, Putu Eka Dambayana; Sudana, Putu Ayu Prabawati (ppjbsip, 2025)
This study aims, first, to analyze the realization of centripetal, centrifugal, and blurring forces in the implementation of language policies on campus public signage in Bali. Second, it seeks to map the positioning of national and regional language policies through the lens of heteroglossia. This research adopts a qualitative approach with a descriptive method. The subjects of the study include campus outdoor signs, campus management representatives, and students who were selected purposively. The study was conducted at five campuses in Bali, namely, Universitas Pendidikan Ganesha (UPG), Universitas Panji Sakti (UPS), STAHN Mpu Kuturan (MK), Monarch Singaraja (MS), and H.I Singaraja (HIS). Data were collected through observations, including photographing all campus public signs, and conducting interviews with campus management representatives and students. The data were analyzed using a descriptive-interpretative method. The study finds that centripetal and centrifugal language forces are evident in campus public signs through the utilization of particular languages. Indonesian, as the national language, strongly represents the centripetal force. Meanwhile, foreign languages such as English and regional languages like Balinese and Old Javanese signify the centrifugal force. These forces converge in blurring areas, where Indonesian, foreign languages, and regional languages are used simultaneously on the same public signs. The interaction between the centripetal and centrifugal forces is also evident in national and regional language regulations that support heteroglossia in campus public signage. Abstrak Penelitian ini bertujuan, pertama, untuk menganalisis realisasi daya sentripetal, sentrifugal, dan kekaburan dalam implementasi kebijakan bahasa pada tanda luar ruang publik di lingkungan kampus di Bali. Kedua, kajian ini bertujuan untuk memetakan posisi kebijakan bahasa nasional dan daerah melalui perspektif heteroglosia. Pendekatan yang dipakai adalah pendekatan kualitatif dengan metode deskriptif. Subjek penelitian ini meliputi tanda luar ruang kampus, perwakilan manajemen kampus, dan mahasiswa yang dipilih secara purposif. Penelitian dilakukan di lima kampus di Bali, yaitu Universitas Pendidikan Ganesha (UPG), Universitas Panji Sakti (UPS), STAHN Mpu Kuturan (MK), Monarch Singaraja (MS), dan H.I Singaraja (HIS). Data dikumpulkan melalui observasi, termasuk memotret semua tanda luar ruang kampus, dan melakukan wawancara dengan perwakilan manajemen kampus dan mahasiswa. Data dianalisis menggunakan metode deskriptif-interpretatif. Penelitian ini menemukan bahwa daya bahasa sentripetal dan sentrifugal terlihat jelas pada tanda luar ruang publik kampus melalui penggunaan bahasa-bahasa tertentu. Bahasa Indonesia, sebagai bahasa nasional, merepresentasikan daya sentripetal. Sementara itu, bahasa asing, terutama bahasa Inggris, dan bahasa daerah seperti bahasa Bali dan Jawa Kuno menunjukkan daya sentrifugal. Kedua daya ini bertemu di area kekaburan, di mana bahasa Indonesia, bahasa asing, dan bahasa daerah digunakan secara bersamaan pada tanda luar ruang publik yang sama. Interaksi antara daya sentripetal dan sentrifugal juga terlihat pada peraturan bahasa nasional dan daerah yang mendukung heteroglosia pada tanda luar ruang kampus.